Pedagogical content knowledge of French as a foreign language: differences between pre-service and in-service teachers. Issue 4 (4th July 2019) - Evens, Marie; Tielemans, Kelly; Elen, Jan; Depaepe, Fien
Abstract: Pedagogical content knowledge (PCK) is an important predictor of educational quality. PCK develops from various sources, such as teaching experience. Studies investigating the effects of teaching experience on PCK development mainly focus on the question whether experienced teachers differ from novices in the amount of PCK. In a mixed methods study, we study both quantitative and qualitative differences between pre-service and in-service teachers' PCK. Total scores on a paper-and-pencil instrument are used as a measure of French PCK. To analyse the participants' PCK in a qualitative way, answers are coded in four categories and the prevalence of answers in each category is compared between groups. Furthermore, the nature of answers is studied. No differences on our quantitative PCK measure are observed. The qualitative analysis shows that in-service teachers have more difficulties with conceptual knowledge, while showing more practical knowledge of students' understanding than pre-service teachers.